Efforts of The Village Government In Enforcing Farm Animal Control In Bangunemo Village, North Bulagi District, Banggai Kepulauan District - Amane, Ade Putra Ode; Jayalangi, La Ode Sabirila; Matorang, Haminun Dg. (Socious Journal, 2024)
The control of livestock is one of the main factors that needs to be considered by the village government, because the presence of livestock that has been roaming freely in the Bangunemo Village area and has damaged yards, plants, plantation/agricultural products and disrupted road traffic, thus creating disputes between fellow residents which has an impact on disrupting public order and tranquility. This research was conducted in Bangunemo Village with the aim of determining the extent of the Village Government's efforts in carrying out its duties and responsibilities as a good government in enforcing the control of livestock in Bangunemo Village. Data collection methods used, Observation, Questionnaire and Documentation. The types of data sources used are primary data and secondary data. the population of the researcher is the Bangunemo village community totaling 276 people. The sampling technique in this study uses the Slovin formula using a purposive approach to make it easier for researchers to research and the number of samples in this study is 38 people. The data analysis used is qualitative descriptive analysis which includes processing, data explanation and drawing conclusions. The results of the study variable (X) Village Government Efforts with an average of 64%, and variable (Y) Livestock Control in Bangunemo Village with an average of 73%. So 64 + 73 = 137 : 2 = 68%, it is concluded that the Village Government's Efforts in Enforcing the Order of Livestock in Bangunemo Village, North Bulagi District, Banggai Islands Regency were carried out well with a percentage of 68%.